Casting Issues of Thick-Walled High Pressure Die Castings - Molnár, Dániel; Kiss, Ádám; Majoros, Csaba (International Journal of Engineering and Management Sciences, 2020)
Die casting is a manufacturing process for producing accurately dimensioned, sharply defined, smooth or textured surface metal parts. It is accomplished by injecting liquid metal at fast velocity and under high pressure into reusable steel dies. Compared to other casting processes, die casting is at the top end of both velocity and pressure. The high velocity translates into a very turbulent flow condition. The process is often described as the shortest distance between raw material and the finished product.Pre-fill is a process technique that is the result of significantly delaying the start of fast shot beyond the “metal at the gate” position. It can be stated as a percentage of cavity fill or as a distance beyond metal at the gate.